2022
DOI: 10.1073/pnas.2108666119
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multidimensional impacts of active learning revealed in a first implementation in the MENA region

Abstract: Enhancing science education in developing countries has been a focal point of many studies and efforts, but reform has mainly been driven by top-down approaches that often face impediments. A shift to active learning pedagogies can potentially address these challenges, but it has thus far been predominantly implemented and understood in developed countries. Thanks to the growing accessibility of open education resources and ubiquitous technologies, education reform can now be carried out from the bottom up. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…More recently, Ibrahim et al. (2022) reported a 2‐year study of active learning in physics and astronomy courses involving 2145 students in the Middle East and Northern Africa. They found positive effects of active learning (e.g.…”
Section: Possible Strategies To Address Student Disengagementmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Ibrahim et al. (2022) reported a 2‐year study of active learning in physics and astronomy courses involving 2145 students in the Middle East and Northern Africa. They found positive effects of active learning (e.g.…”
Section: Possible Strategies To Address Student Disengagementmentioning
confidence: 99%
“…Active learning can also narrow achievement gaps in examination scores by 33% and passing rate by 45% for students underrepresented in STEM compared to lecture (Theobald et al, 2020). More recently, Ibrahim et al (2022) reported a 2-year study of active learning in physics and astronomy courses involving 2145 students in the Middle East and Northern Africa. They found positive effects of active learning (e.g.…”
Section: Promoting Active Learning Through the Use Of Online Flipped ...mentioning
confidence: 99%
“…Ibrahim, Sulaiman, and Ali ( 10 ) carry out their careful examination of active learning in the Middle East and Northern Africa (MENA) and are conscious of the stakes. People less than 30 years old are 55% of the population of the MENA region.…”
mentioning
confidence: 99%
“…On the other hand, they are harshly critical of available university education in the sciences: “Outdated and disengaging science education, which teaches science as a body of facts, and assesses mainly on rote-memorization, does not only turn youth away from STEM disciplines … but also degrades the overall learning and skill-outcomes of the graduates. ( 10 )”…”
mentioning
confidence: 99%